Value of character education in qs. Luqman[31]: 18 (Analysis of Ma’na Cum Maghza) - Atiqoh Firdaus; Maula Sari (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
This paper describes the values of character education in QS. Luqman: 18 and aims that the public can understand character education according to the teachings of the Qur'an and see the significance contained in the QS. Luqman: 18 by using the ma'na cum maghza approach today, especially in Indonesia. This research is included in qualitative research that uses literature review or library research to reveal the values of character education contained in QS. Luqman: 18. The results of the research in this paper are that QS. Luqman: 18 contains the values of character education by being humble, not arrogant, friendly to everyone, and walking with a polite attitude. QS. Luqman:18 this was revealed due to a question from a Quraysh regarding the story of Luqman and his son